COMMUNITY INTERVENTIONS TO REDUCE MATERNAL MORTALITY IN LOW-RESOURCE AREAS - Djosci Coêlho de Sá, Henrique; Costa de Mello Farah, Vinicius; Fernandes Alevato, Lucca; Sérgio Martins Neto, José; Víctor Elias Sobrinho, Paulo; Andre Ramalho Rangel Lima, Paulo; Bandeira de Mello Sanches de Almeida, Eduardo; Hugo Mendes da Cunha, Vitor; Vitor Gullo de Oliveira Ribeiro, Antônio; Tibério Campos Calegário, Luiza; Zanetti Pinheiro, Thiago (Health and Society, 2024)
Maternal mortality, defined as the death of women during pregnancy, childbirth or in the postpartum period, continues to be a serious public health problem, especially in low-resource areas. Factors such as limited access to quality healthcare, lack of infrastructure, shortage of qualified professionals and socio-economic inequalities contribute to high mortality rates. In many of these regions, community interventions have been key to reducing maternal mortality by providing direct assistance to pregnant women, promoting health care education and strengthening the link between communities and medical services. This study seeks to analyze community interventions implemented in low-resource areas to reduce maternal mortality, evaluating their strategies, challenges and the results obtained in improving maternal survival rates. This study is a systematic review that investigates the effectiveness of maternal health interventions in low- and middle-income countries, focusing on skilled birth attendant programs, community transport, and technological innovations. The analyses were carried out in databases such as PubMed, BMC Pregnancy and Childbirth and African Journal of Reproductive Health, using data from articles published between 2015 and 2021. Community interventions to reduce maternal mortality range from health education programs, training traditional birth attendants and strengthening maternal and child support networks. One of the main approaches involves training community health agents, who work directly in communities, providing basic prenatal care, referral to medical services in cases of risk and promoting knowledge about signs of pregnancy complications. These actions are especially important in remote areas, where access to health facilities is limited. Another key aspect of these interventions is the promotion of safe practices during childbirth and the strengthening of emergency transport systems, ensuring that pregnant women at risk can be transferred to health centers equipped to deal with complications. The introduction of simple technologies, such as clean delivery kits and essential medicines, has shown promising results in reducing infections and hemorrhages, which are primary causes of maternal mortality. Awareness campaigns also play a crucial role, educating the population about the importance of prenatal care, proper nutrition and birth assistance in controlled environments. These initiatives aim not only to improve knowledge about maternal health, but also to combat cultural and social barriers that can prevent pregnant women from seeking medical care in a timely manner. It is concluded that community interventions have proven to be an effective approach to reducing maternal mortality in low-resource areas. Training health workers, implementing safe delivery practices and raising awareness about antenatal care are strategies that have contributed significantly to improving maternal health outcomes. However, for these interventions to be sustainable and scaled up, continued public policy support, adequate funding and the integration of these actions with formal health systems are essential.